Kapitalisme dalam Pandangan Filsafat Bisnis Islam - Rahmat Afrizon Harianja; Syarifuddin (Universitas Muhammadiyah Surabaya, 2025)
The purpose of this study is to find out capitalism in the view of Islamic business philosophy, Capitalism is the dominant economic system in the modern world, but is often considered contrary to moral and ethical values in various traditions, including in Islamic business philosophy. This research uses a qualitative method (seeking meaning from an understanding) using a library research approach, this research shows that although capitalism can provide economic benefits, it also leaves challenges in terms of ethics and justice. Islamic business philosophy offers an alternative that emphasizes the welfare of society, ethics in transactions, and social responsibility as cornerstones in the development of a more sustainable economic system. As such, this study contributes to a deeper understanding of the integration of Islamic values in business practices and the challenges and opportunities for capitalism in the context of a society that emphasizes spiritual and moral values.